Kajian Semantik Karakteristik Makna Syair Dendang Danau Bungara Kecamatan Kota Baharu Kabupaten Aceh Singkil - Yuliana Sinaga; Meri Yulizar; Wina Almunadia (Jurnal Serambi Ilmu, 2025)
This study examines the characteristics of meaning in dendang poetry within the Dampeng Dance tradition in Gampong Danau Bungara, Kota Baharu District, Aceh Singkil Regency. The research is motivated by the importance of preserving the Singkil community’s oral tradition, which is rich in cultural values but increasingly less understood by the younger generation. The aim is to describe the types of meanings contained in dendang poetry and its social functions. The study applies a qualitative descriptive method with a semantic analysis approach. Data were collected through observations of Dampeng Dance performances, interviews with pengkhulu khonde (dendang poets) and traditional leaders, as well as oral and written documentation. Data analysis refers to Fang and Chaer’s semantic theory, covering lexical, grammatical, contextual, referential, non-referential, denotative, connotative, conceptual, and associative meanings. The findings reveal that dendang poetry takes the form of Aceh Singkil pantun with distinctive rhyme and rhythm patterns, containing prayers, moral advice, religious values, and serving as entertainment, education, cultural communication, and identity preservation.